In Front of the Lens: The Expectations, Experiences, and Reactions of Visual Journalism's Subjects. (March 2019) - Thomson, T. J.
Visual journalism is a curious form of interaction usually involving strangers who have their private lives transformed—wittingly or not—into public objects of attention. Sometimes the interaction between journalist and subject is extended and in-depth, sometimes it is brief and shallow, and sometimes it is nonexistent. People are often reactive to cameras, and tension can exist between the idealized ways people want to be depicted and the ways journalists visually render them. Considering that visual media are "complex reflections of a relationship between maker and subject in which both play roles in shaping their character and content, " scholars have called for more research on journalists' subjects and how they behave in front of the visual news media. This work answers that call and provides one of the first empirical glimpses into how people regard the experience of being photographed and video-recorded by journalists. As a primary arc of the work is concerned with the nature of experience, it adopts a phenomenological approach and seeks to identify (a) the expectations that news media subjects have of visual journalists, (b) how journalists' subjects perceive the experience of being photographed and video-recorded in a news media context, and (c) how the subject's identities and representational aspirations affect their perception of the imaging event. These questions are explored through a four-pronged approach: (a) nonparticipant observations, (b) word association exercises, (c) in-depth interviews, and (d) photo-elicitations. The findings suggest that subjects are more outcome- rather than process-focused; that technological changes and resulting behavior shifts are altering the nature of reality and experience, which has implications for privacy and consent; and that perception is quite fluid and can be affected by identity, habituation, and emotionally valenced experiences.